Transforming English Language Learning through Blended Learning: A Systematic Analysis of Effectiveness, Barriers, and Technology Readiness in the Context of Higher Education - Irsyad, Syifa Fauziah; Ramadhan, Syahrul; Mukhaiyar, Mukhaiyar (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
This literature review focuses on the study of the effectiveness of blended learning models in developing English language skills in higher education. This study aims to analyze the role of blended learning in improving language skills and technological readiness and identifying barriers faced in its implementation. This study is a systematic literature review that uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines as a model in the process of selecting and analysing literature data conducted on 30 articles from national and international journals indexed by Scopus and Sinta 2 and 3. The study results indicate that blended learning can significantly contribute to students' English skills. Still, its effectiveness is highly dependent on the support of technological infrastructure and the technical skills of users. Barriers such as limited internet access, gaps in technological knowledge, and preferences for face-to-face learning are obstacles that need to be overcome to optimize this model. The implications of this study highlight the importance of developing technological infrastructure, special training for lecturers and students, and more adaptive learning designs to optimize blended learning in higher education. This study contributes to providing comprehensive insights into modern learning strategies in the digital era